Application of Contextual Learning Based on Madura Local Culture in Improving Understanding of Social Values in Early Childhood - Danang Prastyo; Gunarti Dwi Lestari; Nunuk Haryati; Desika Putri Mardiani; Ardhana Reswari (Universitas Pendidikan Ganesha, 2025)
Local culture plays an important role in shaping early childhood character, yet its implementation in kindergarten remains limited, hindering the integration of social values such as cooperation, togetherness, and cultural identity. This study aims to examine the implementation of contextual learning based on Madurese local culture in enhancing young children’s understanding of social values. The research employs a qualitative approach using a case study method. Data were collected through observations and in-depth interviews with three informants: one kindergarten principal and two kindergarten teachers. Observations were conducted during cultural activities, such as the celebration of the Prophet Muhammad’s birthday (Maulid Nabi Muhammad SAW), the torch parade on the evening of 1 Muharram, and the introduction of Madurese traditional clothing, which represent the implementation of social values through local culture-based learning. The results show that local culture-based learning is effective in instilling social values such as mutual cooperation, togetherness, and pride in cultural identity. The contextual approach based on local culture in kindergarten also effectively connects learning materials to children’s daily lives, making them relevant and meaningful. Through direct experiences in cultural activities, children develop social skills, creativity, and problem-solving abilities. This learning approach also strengthens the relationship between children, teachers, parents, and the community, while fostering pride in local cultural identity. Overall, this approach supports holistic child development, socially, emotionally, and intellectually.